Adesmia pinifolia, a Native High-Andean Species, as a Potential Candidate for Phytoremediation of Cd and Hg - Parera, Victoria (2024)
This study highlights Adesmia pinifolia, a native high-Andean species, as a potential candidate for the phytoremediation of soils contaminated with Cd and Hg. In this work, a semi-hydronic assay with different doses of Cd (3, 4.5, and 6 mg L−1) and Hg (0.8, 1.2, and 1.6 mg L−1) was analysed to evaluate the establishment of plants, antioxidant defence systems, oxidative stress, and the ability to accumulate heavy metals. The results indicate high survival rates (>80%); however, Cd significantly reduced shoot and root biomass, while Hg increased root biomass with the 1.6 mg L−1 treatment. Cd and Hg tend to accumulate more in roots (2534.24 µg/g and 596.4 µg g−1, respectively) compared to shoots (398.53 µg g−1 and 140.8 µg g−1, respectively). A significant decrease in the bioconcentration factor of Cd and Hg in roots was observed as metal levels increased, reaching the maximum value at 3 mg L−1 (805.59 ± 54.38) and 0.8 mg L−1 (804.54 ± 38.09). The translocation factor, <1 for both metals, suggests that translocation from roots to shoots is limited. An overproduction of reactive oxygen species (ROS) was observed, causing lipid peroxidation and oxidative damage to plant membranes. Tolerance strategies against subsequent toxicity indicate that enhanced glutathione reductase (GR) activity and glutathione (GSH) accumulation modulate Cd and Hg accumulation, toxicity, and tolerance.